2021
DOI: 10.3390/app11073277
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postural Stability and Regulation among Female Athletes from Different Sports

Abstract: The aim of this study was to evaluate the postural regulation of female athletes who participate in different sports under normal and high-demand conditions. Fifty-nine female athletes were classified into four specific groups based on their individual sport, which included basketball (n = 16), gymnastics (n = 10), ski jumping (n = 13), diving (n = 8), and one group of recreational athletes (n = 12). These groups were then compared using several posturographic tests under four bipedal conditions: eyes open or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Our findings support previous research, which has suggested that more demanding test positions demonstrate greater betweengroup differences [20]. These results also partially support the findings of Lauenroth et al [3], who assessed the postural stability of female athletes from a variety of sports and found that gymnasts had superior control over the athletes from the team-based sports. Davlin [21] used a stabilometer to assess dynamic balance and found that gymnasts had better postural control than soccer players and swimmers.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings support previous research, which has suggested that more demanding test positions demonstrate greater betweengroup differences [20]. These results also partially support the findings of Lauenroth et al [3], who assessed the postural stability of female athletes from a variety of sports and found that gymnasts had superior control over the athletes from the team-based sports. Davlin [21] used a stabilometer to assess dynamic balance and found that gymnasts had better postural control than soccer players and swimmers.…”
Section: Discussionsupporting
confidence: 92%
“…Not only is this control critical in activities of daily living to prevent falls, but this system can be taxed even more during competitive athletics when the kinematics and kinetics required by a particular sport are increased substantially. As such, deficiencies in an athlete's postural control can result in decreased performance and potential injury [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experienced Polish gymnasts (seniors) are characterized by superior values of balance for standing positions and handstands, compared to younger gymnasts (juniors), so the long-term practice of this sport will ensure a higher level of static balance [91]. The postural stability analysis at the level of women athletes identified superior values of technical sports practitioners (first, gymnastics, then ski jumping and diving) by comparison with basketball athletes and leisure/recreational athletes [92]. The absence of these types of sports in our group does not allow us to comment on the data provided by the research mentioned.…”
Section: Comparison Of Results With Similar Studies Related To Balanc...mentioning
confidence: 99%